Differential susceptibility to SARS‐CoV‐2 in the normal nasal mucosa and in chronic sinusitis. Issue 8 (14th May 2022) - Zhang, Zhili; Peng, Haoran; Lai, Ju; Jiang, Liangliang; Wang, Liefu; Jin, Shengkai; Fan, Kai; Zhang, Zimu; Zhao, Chuanliang; Deng, Dan; Zhao, Ping; Gao, Zhengliang; et al.
Abstract: Human nasal mucosa is susceptible to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and serves as a reservoir for viral replication before spreading to other organs (e.g. the lung and brain) and transmission to other individuals. Chronic rhinosinusitis (CRS) is a common respiratory tract disease and there is evidence suggesting that susceptibility to SARS‐CoV‐2 infection differs between the two known subtypes, eosinophilic CRS and non‐ECRS (NECRS). However, the mechanism of SARS‐CoV‐2 infection in the human nasal mucosa and its association with CRS has not been experimentally validated. In this study, we investigated whether the human nasal mucosa is susceptible to SARS‐CoV‐2 infection and how different endotypes of CRS impact on viral infection and progression. Primary human nasal mucosa tissue culture revealed highly efficient SARS‐CoV‐2 viral infection and production, with particularly high susceptibility in the NECRS group. The gene expression differences suggested that human nasal mucosa is highly susceptible to SARS‐CoV‐2 infection, presumably due to an increase in ACE2‐expressing cells and a deficiency in antiviral immune response, especially for NECRS. Importantly, patients with NECRS may be at a particularly high risk of viral infection and transmission, and therefore, close monitoring should be considered. Abstract : Human nasal mucosa can be infected by SARS‐Cov‐2 because ACE2 is wildly expressed through the mucosa. We culture the tissues in vitro to mimic the infection progress. The results provide that non‐eosinophilic CRS (NECRS) tissue is more sensitive to SARS‐Cov‐2 infection than eosinophilic CRS (ECRS) tissue and healthy control.